Empowering Employee Engagement: The Mediating Role Of Job Satisfaction In The Influence Of Islamic Work Values - Nitami Galih Pangesti; Candraningrat Candraningrat (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2025)
This study examines the positive influence of Islamic Work Values (IWV) on employee job satisfaction and engagement, with job satisfaction acting as a mediator in this relationship. Islamic Work Values, rooted in Islamic ethical and moral teachings, encourage behaviours such as integrity, fairness, and accountability, which promote positive interactions and a supportive work environment. This study is a quantitative study with a sample size of 100 employees. The results of this study explain that there is an influence between Islamic work values and employee engagement and job satisfaction as a mediator.